Relation between invasive hemodynamics and measured glomerular filtration rate by 51Cr-EDTA clearance in advanced heart failure. (3rd April 2019) - Deis, Tania; Balling, Louise; Boesgaard, Søren; Rossing, Kasper; Schou, Morten; Oturai, Peter; Wolsk, Emil; Gustafsson, Finn
Abstract: The interaction between hemodynamics and kidney function in heart failure (HF) is incompletely understood. We investigated the association between invasive hemodynamic parameters and measured glomerular filtration rate (mGFR) by plasma clearance of 51-chromium-labeled ethylenediamine tetra-acetic acid ( 51 Cr-EDTA) in patients with advanced HF and tested the hypothesis that patients with reduced mGFR have lower cardiac index (CI) and mean arterial pressure (MAP) as well as higher central venous pressure (CVP) and pulmonary capillary wedge pressure (PCWP). We retrospectively studied 242 patients (mean age 50 ± 13 years) referred for evaluation for heart transplantation or implantation of a left ventricular assist device with a left ventricular ejection fraction < 45% on optimal medical therapy, who underwent right heart catheterization (RHC) and measurement of 51 Cr-EDTA clearance. Mean mGFR was 63 ± 21 mL/min/1.73 m 2, CI was 2.3 ± 0.7 L/min/m 2, PCWP was 21 ± 9 mmHg, and CVP was 10.3 ± 5.2 mmHg. Univariate analysis demonstrated a significant correlation between mGFR and CI ( r 2 = 0.030, p  = .007) and CVP ( r 2 = 0.017, p  = .049) but not between mGFR and MAP or PCWP. In multivariate analyses, none of the hemodynamic variables remained significantly associated with mGFR. While CVP and CI were correlated with mGFR in univariate analysis the results of analyses adjusted for multiple covariates suggest that hemodynamics are only correlated to renal function in advanced HF to a modest degree challenging the hypothesis that renal dysfunction in HF mainly is a consequence of renal congestion.